(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Background: Hospital-acquired infections (HAIs) are a growing worldwide issue, leading to increase in-hospital mortality, prolonged patient stays, and escalating healthcare expenses. This study investigates the patterns of antibiotic resistance and the variability of harmful microorganisms on surfaces across different departments within Al-Muthanna Hospitals in Iraq. The severity of these infections is influenced by the specific characteristics of the microorganisms present, as well as the prevalence of antibiotic-resistant pathogens in hospital environments. Methods: A study was reached between October 1, 2024, to December 30, 2024. A collection of samples was made by swabbing surfaces in the hospital, and the isolated bacteria were tested for antibiotic susceptibility using the Kirby-Bauer disk diffusion methods, following the standards set by the CLSI. Results: %99 of (100) swab samples had positive growth, a total of one hundred twenty microorganisms were isolated. The most frequently identified organisms were as follows: 40 (33.3%) Staphylococcus aureus , 29 (24.2%) Pseudomonas aeruginosa, 12 (10%) Escherichia coli , 11 (9.2%) Enterococcus species, and 9 (7.5%) each of Candida albicans and Klebsiella pneumoniae. Additionally, 6 (5%) of the isolates were Proteus and Shigella, all of which were multidrug-resistant (MDR). Conclusions: Antimicrobial resistance is a significant issue in hospitals. Alongside the careful use of antibiotics, we recommend ongoing and thorough monitoring of multidrug-resistant (MDR) bacteria to effectively manage antimicrobial resistance among pathogens.